Analysis of Geometry Problem Solving Based on APOS Theory for Class IX Students - Fina Mifta Vebianti; Sunardi Sunardi; Abi Suwito; Dinawati Trapsilasiwi; Ervin Oktavianingtyas (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
This study aims to describe students geometry problem solving abilities based on APOS theory in terms of field dependent and field independent cognitive styles. This type of research is descriptive research with a qualitative approach. The research subjects were 4 students of class IX SMPN 1 Jember which were grouped based on cognitive style, namely 2 students with field independent cognitive style and 2 students with field dependent cognitive style. Methods of data collection using problem solving tests and interviews. The results of data analysis show that FD students tend to be able to write and mention information in questions, but still have difficulty in explaining the meaning of the questions. FI students tend to be able to write and explain information on questions. At the process stage, FI and FD students were able to model and explain the stages well, but FD still had errors in changing the shape of the mathematical model correctly. At the object stage, FI students work on questions freely, while FD students work on questions in detail or fixate on structured steps, FD students also have difficulty explaining their work. At the schema stage, FI and FD students can explain how to use the information in the problem, but FD students still experience errors from the process stage to drawing conclusions as a solution. Field independent students tend to be free or not fixated on complete and detailed steps, while field dependent students tend to be bound or fixated on complete and detailed steps.